2006
DOI: 10.1021/bi060767p
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Down Regulation of Photosynthesis by Blue Light in the Cyanobacterium Synechocystis sp. PCC 6803

Abstract: Exposure to blue light has previously been shown to induce the reversible quenching of fluorescence in cyanobacteria, indicative of a photoprotective mechanism responsible for the down regulation of photosynthesis. We have investigated the molecular mechanism behind fluorescence quenching by characterizing changes in excitation energy transfer through the phycobilin pigments of the phycobilisome to chlorophyll with steady-state and time-resolved fluorescence excitation and emission spectroscopy. Quenching was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
54
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 31 publications
(47 reference statements)
6
54
0
Order By: Relevance
“…Following induction of NPQ, the quenching could be sustained in the dark by the addition of 3% (v/v) of a protein cross-linker, glutaraldehyde, 10 s prior to removing the actinic illumination. A similar technique has previously been used to sustain NPQ present in cyanobacteria (31). The absence of NPQ relaxation was confirmed by application of saturating light pulses (Fig.…”
mentioning
confidence: 65%
“…Following induction of NPQ, the quenching could be sustained in the dark by the addition of 3% (v/v) of a protein cross-linker, glutaraldehyde, 10 s prior to removing the actinic illumination. A similar technique has previously been used to sustain NPQ present in cyanobacteria (31). The absence of NPQ relaxation was confirmed by application of saturating light pulses (Fig.…”
mentioning
confidence: 65%
“…In contrast, the mechanism of thermal energy dissipation in cyanobacteria, which plays a key role in global carbon cycling, remained elusive. Only within the last few years has a photoprotective mechanism associated with the soluble phycobilisome antenna of PSII in cyanobacteria been demonstrated (8)(9)(10)(11)(12)(13)(14). A specific soluble carotenoid protein, the orange carotenoid protein (OCP), plays an essential role in this process (9,10).…”
mentioning
confidence: 99%
“…Surprisingly, the role of the carotenoid in the OCP is completely different from the role of the photoprotective carotenoids in plants. The OCP appears to act as a photoreceptor, responding to blue-green light; this induces energy dissipation, resulting in a detectable quenching of the cellular fluorescence, known as nonphotochemical-quenching (NPQ), through interaction with the phycobilisome (9,11). In mutants containing the OCP but lacking phycobilisomes, blue-green light was unable to induce the photoprotective mechanism (9,10).…”
mentioning
confidence: 99%
“…It has been recently shown that, in cyanobacteria, like in plants, there exists a photoprotective process that decreases the energy transfer between the antenna and the reaction centers by increasing thermal dissipation (8)(9)(10)(11)(12)(13). However, this mechanism is not triggered by a lowering of the luminal pH, as occurs in plants;…”
mentioning
confidence: 99%